Pelatihan tembang macapat dengan pendekatan langsung di SD Kanisius Sorowajan Yogyakarta - Gregorius Ari Nugrahanta; Eko Hari Parmadi; Fransisca Tjandrasih Adji; Margaretha Widiastuti Rusmala Dewi; Maria Theresia Cinta Kasih; Berliana Putri Yangga Puspita; Cindy Gupita Sari; Brigita Sherlyta Erlansa Putri; Hilary Relita Vertikasari Sekarningrum (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The lack of understanding about macapat songs among teachers and the lack of an effective learning model for teaching macapat songs to students was the background of this activity. This activity aimed to improve the ability of macapat songs with a direct approach for teachers at SD Kanisius Sorowajan Yogyakarta. The direct learning approach was an approach that provided opportunities for students to learn by observing, researching, and imitating the actions exemplified by the teacher in class. The ability of macapat songs was described in four indicators, namely scope, preservation, notation, and classification of macapat songs. The method used in this activity was a participatory assessment involving 11 teachers from SD Kanisius Sorowajan Yogyakarta. The results of the activity showed 1) an increase in pretest to posttest scores of 76.70%, 2) a significant effect on the teacher's macapat song ability (p < 0.05) which was included in the large effect category (r = 0.9552), and 3 ) a high level of effectiveness of the training implemented (n-gain score 76.09%).